Steak Location Within the Semitendinosus Muscle Impacts Metmyoglobin Accumulation on Steaks During Retail Display - K. J. Phelps; T. G. O'Quinn; T. A. Houser; J. M. Gonzalez (Kansas Agricultural Experiment Station Research Reports, 2017)
Beef color is a major attribute consumers utilize to make purchasing decisions. It is estimated poor color shelf-life of beef steaks costs the meat industry more than 1 billion annually. Shelf-life color is influenced by a balance of two biochemical processes within steaks: metmyoglobin reducing ability and oxygen consumption. Steaks that exhibit a greater metmyoglobin reducing and a reduced oxygen consumption are typically characterized as more color stable. Characteristics of the muscle fiber or muscle cell are what determine the properties of a steak. Commonly, muscles with more oxidative fibers have an elevated oxygen consumption and reduced metmyoglobin reducing ability. The Semitendinosus muscle or eye of round possesses a divergent muscle fiber isoform distribution based on the location steaks are fabricated. The objective of this study was to examine effects of steak location on muscle fiber type distribution and metmyoglobin accumulation of Semitendinosus steaks.
Keywords: color stability; muscle fiber type; Semitendinosus